Studi Komparasi Sikap Kerja dengan Kejadian Low Back Pain Pada Perajin Rebana Desa Bungah Kecamatan Bungah Kabupaten Gresik - Inayah, Zufra; Supiyatun, Supiyatun (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Musculoskeletal is a system that often experiences increased loads and injuries in every job, including tambourine craftsmen. Data shows that 95% of tambourine craftsmen experience musculoskeletal complaints, of which 55% occur in the lower back area, 20% in the right shoulder area, 15% in the left shoulder area and 10% experience cramps. Objective: This research is to analyze the comparison of work attitudes with the incidence of lower back pain in tambourine craftsmen in Bungah Village, Bungah District, Gresik Regency). Method: Cross sectional survey research design with observation. The population is all tambourine craftsmen in Bungah Village, Bungah District, Gresik Regency, totaling 150 people. Meanwhile, the sample size was 110 respondents taken using simple random sampling. The independent variables are sitting work attitude and standing work attitude, while the dependent variable is the incidence of low back pain. The instrument uses a closed questionnaire. Analysis uses the Chi-Square test with alpha 0.05. Results: Research shows that almost all of the working attitudes of tambourine craftsmen (83.6%) are ergonomic sitting working attitudes, while the majority (69.1%) are standing working attitudes with low risk. Almost all complaints of low back pain among tambourine crafters (79.1%) were not low back pain. The Chi-Square test results for the sitting work attitude have a p value = 0.000 < 0.05 with OR = 18.400, and for the standing work attitude the p value = 0.000 < 0.05 with OR = 3.091. Conclusion: There is a difference in work attitude regarding the incidence of low back pain in tambourine craftsmen with a sitting work attitude having a greater risk level than standing. Monotonous work positions should be avoided and stretching should be done so that muscles do not become stiff and symptoms of lower back pain can be avoided.